Morphological diversity and genetic potential of Aloe barbadensis Mill. accessions from diverse agro-climatic regions of Tamil Nadu, India - Abinaya, C; Suresh, J; Sundar, S T B; Kokiladevi, E; Uma, D; Bharathi, N (Plant Science Today, 2025)
Aloe barbadensis Mill. is a medicinal plant of great importance, widely cultivated for its therapeutic properties. However, limited research has been conducted on the morphological diversity of Aloe vera germplasm in India. This study assessed the morphological diversity of 40 A. vera accessions collected from different agro-climatic regions in Tamil Nadu, India. Eight quantitative morphological descriptors were evaluated. Significant variations were observed for all the studied traits, indicating substantial morphological diversity among the accessions. Principal component analysis revealed that the first three principal components (PC’s) accounted for 72.90% of the total variation. Cluster analysis grouped the accessions into three main clusters based on morphological similarity. Associations were found between several traits, with correlation analysis showing significant positive correlations between plant size, leaf dimensions and yield-related traits. High broad-sense heritability estimates were observed for several characteristics, suggesting the potential for genetic improvement through selection. The findings highlight the morphological diversity in Tamil Nadu A. vera germplasm, which can be exploited for the genetic improvement and development of effective conservation strategies for this valuable medicinal plant. The morphological diversity observed in this study can be attributed to the diverse agro-climatic conditions and geographical locations from which the accessions were collected.